The Place of Technology in the Evolution of Modern Trade Fairs - PROSZOWSKA, Anita (Journal of Environmental Management and Tourism, 2025)
This article analyses changes in the functioning of the trade fair sector resulting from the emergence of new technologies and identifies their place in the evolution of these business events. It considers particularly important the extent to which trade show stakeholders are prepared to use new technologies to achieve trade show objectives, which technologies are considered most beneficial and what prospects they have for development. The paper reviews the relevant literature, analyses existing solutions and reports on interviews with representatives of trade fair organisers and operators. The choice of respondents was dictated by the fact that they have to plan well in advance for investments in new technological solutions to use at trade fairs in the future and therefore they carefully analyse market developments and the expectations and technological capabilities of their stakeholders. The future of trade fairs depends on the resilience of the sector, which is facilitated by increased implementation of IT solutions at trade fairs. One trend is to use existing technologies in new ways ( e.g. QR codes). One threat to the effectiveness of trade fair objectives arising from the presence of new technologies is the varying level of technological sophistication of individual participants – the high technological sophistication of some participants may make it challenging to build relationships with less advanced participants. Implementing digital solutions involves large financial outlays during the initial implementation period. However, implementing them usually makes it possible to very quickly reduce the costs of trade fair participation (by better targeting activities), to conduct more accurate analyses of the effectiveness of activities and to optimise the allocation of financial resources (by more completely interpretating data and identifying the most effective strategies). Traditional trade fair technologies associated with the construction of stands are a source of high costs and much waste after the event. Using modern technologies in trade fair management offers an opportunity to implement pro-environmental solutions in trade fair marketing. The paper analysis how emerging technologies, particularly artificial intelligence, are reshaping trade fairs into highly coordinated, technology-driven business platforms. It offers unique, real-time empirical evidence from 2024–2025 Polish industry events, capturing evolving stakeholder expectations, opportunities, and barriers to technological adoption in this sector. Additionally, it introduces a novel perspective on balancing digital transformation with economic sustainability and highlights the need for future quantitative research to guide strategic investments in trade fair innovation. This study is limited by its reliance on qualitative insights from industry practitioners, lacking comprehensive quantitative data from exhibitors, visitors, and other stakeholders, which restricts the generalisation of its conclusions. Rapid technological advancements in the trade fair sector also pose a challenge, as findings may quickly become outdated, reducing their long-term applicability for decision-making. Future research should focus on large-scale, coordinated quantitative surveys to better capture evolving stakeholder perspectives and guide sustainable investments in digital trade fair infrastructure. Trade fairs will remain essential for relationship-building and networking, but future success will depend heavily on integrating digital tools to extend engagement beyond physical events. It highlights the need for long-term, well-planned technological investments despite high costs and rapid innovation cycles that risk making solutions obsolete too quickly. The findings emphasise that industry stakeholders must collaborate closely with research centers to guide digital transformation strategies and ensure sustainable, effective trade fair models in a post-pandemic, hybridised market. The paper highlights that post-pandemic trade fairs are evolving into more technology-driven, strategically focused events, shifting from traditional “festival-like” gatherings to structured business tools that prioritise relationship-building. This transformation carries significant social implications, including the need for ongoing digital literacy among stakeholders and a redefinition of networking experiences that balance physical and virtual interactions. However, the high cost and rapid obsolescence of emerging technologies may exacerbate inequalities between more important and smaller exhibitors, potentially reshaping power dynamics within the trade fair ecosystem.